Outer Membrane Vesicles of Helicobacter pylori 7.13 as Adjuvants Promote Protective Efficacy Against Helicobacter pylori Infection - Song, Zifan; Li, Biaoxian; Zhang, Yingxuan; Li, Ruizhen; Ruan, Huan; Wu, Jing; Liu, Qiong (Frontiers in Microbiology, 2020)
Helicobacter pylori (H. pylori), a gram-negative bacterium in the human stomach with global prevalence, is relevant to chronic gastrointestinal diseases. Due to its increasing drug resistance and the low protective efficacy of some anti-H. pylori vaccines, it is necessary to find a suitable adjuvant to improve antigen efficiency. In our previous study, we determined that outer membrane vesicles (OMVs), a multicomponent secretion generated by gram-negative bacteria, of H. pylori were safe and could induce long-term and robust immune responses against H. pylori in mice. In this study, we employed two common vaccines, outer membrane proteins (OMPs) and whole cell vaccine (WCV) to assess the adjuvanticity of OMVs in mice. A standard adjuvant, cholera toxin (CT), was used as a control. Purified H. pylori OMVs used as adjuvants generated lasting anti-H. pylori resistance for 12 weeks. Additionally, both systematic and gastric mucosal immunity, as well as humoral immunity, of mice immunized with vaccine and OMVs combinations were significantly enhanced. Moreover, OMVs efficiently promoted Th1 immune response, but the response was skewed towards Th2 and Th17 immunity when compared with that induced by the CT adjuvant. Most importantly, OMVs as adjuvants enhanced the eradication of H. pylori. Thus, OMVs have potential applications as adjuvants in the development of a new generation of vaccines to treat H. pylori infection.